Analisis Managerial Skill Kepala Sekolah di SD Islam Permata Mojosari Kab. Mojokerto - Miftakul Janah; Hadi Susanto; Sri Mulyani (Jurnal Mahasiswa Manajemen dan Akuntansi, 2025)
This study aimed to analysed managerial skills of the principal of SD Islam Permata Mojosari, focusing on two aspects: developing school plans and leading the school in utilizing school resources, specifically human resources. This study employed a qualitative descriptive approach with data collection methods through observation, interviews, and documentation. Participants in this study included the principal, teachers, staff, school supervisors, school committee chair, and treasurer. Data analysis used the techniques of data reduction, data presentation, and drawing conclusions. The findings indicated that the principal of SD Islam Permata Mojosari demonstrated effective managerial skills in developing school plans. The planning process involved all school members, from the formation of the planning team to monitoring and evaluation. This was evident in the comprehensive and structured strategic plan, annual work plan, and school income and expenditure budget. In leading the school, the principal exhibited effective managerial skills in managing human resources. This was evident in open and collaborative communication with teachers and staff, providing appropriate guidance and motivation, and efforts to improve teacher competence through training and Professional Teacher Group. This study concludes that the managerial skills of the principal of SD Islam Permata Mojosari, Mojokerto Regency, have contributed to improving the quality of education at the school.